Assessment of the impact of organizational structure change on staff working morale: The case of Bank of Africa, Dar es salaam headquarters - Semoka, Navoneiwa (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for the award of the Degree of Master of Business Administration (MBA-Corporate Management) of Mzumbe University